Patent Data for Comparative Study: Case study of Top Aspirants in Bioinformatics Industry - Mago, Neha; Deshpande, Nishad (International Journal of Innovation (São Paulo), 2018)
Innovation and technology are considered as a subject of success and achievement to the firm. The comparative study represents an essential procedure to identify the innovation and technological capabilities of major players involved in the bioinformatics related inventions. The aim of the research is to map out the top firms and identify their strategically important technologies. In view of this, the comparative analysis of major firms in bioinformatics industry is carried out using patent information. Herein the top three assignees are considered and based on this further analysis is performed. The top companies’ trend suggests that Thermo Fisher Scientific Inc. is the major player in bioinformatics research. Thus, we have tried to develop an overview on their patenting trend and important concerned areas of research. Also, our results indicate that the application of computational tools is being utilized for most of the research areas like the study of genomics and proteomics, sequence categorization and their structural prediction.